2011
DOI: 10.1186/1744-859x-10-25
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of a modified release methylphenidate in the treatment of childhood attention deficit hyperactivity disorder

Abstract: Attention deficit hyperactivity disorder (ADHD) is the most commonly diagnosed neurobehavioural disorder in childhood, affecting over 5% of children worldwide. As well as the core symptoms of inattention, hyperactivity and impulsivity, patients often exhibit learning difficulties and impairment in social functioning. The frequency of referral is higher for boys than for girls (about 2:1), and girls are generally older at the time of referral.Pharmacological therapy is considered the first-line treatment for pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…These formulations overcome the need for the multiple daily doses that are necessary with immediate release (IR) formulations because of their short half-life (Takon 2011), and are generally considered to be as effective as the IR formulations (Coghill and Seth 2006). The MR MPH formulations differ in their MPH release profiles, thereby enabling the physician to match the medication to the patient's particular requirements (Takon 2011). Reduced compliance and an increased potential for missed doses have been discussed as potential limitations of IR MPH formulations, together with an uneven coverage through the day and stigmatization by peers when administering IR MPH at lunch time in school (Coghill and Seth 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These formulations overcome the need for the multiple daily doses that are necessary with immediate release (IR) formulations because of their short half-life (Takon 2011), and are generally considered to be as effective as the IR formulations (Coghill and Seth 2006). The MR MPH formulations differ in their MPH release profiles, thereby enabling the physician to match the medication to the patient's particular requirements (Takon 2011). Reduced compliance and an increased potential for missed doses have been discussed as potential limitations of IR MPH formulations, together with an uneven coverage through the day and stigmatization by peers when administering IR MPH at lunch time in school (Coghill and Seth 2006).…”
Section: Introductionmentioning
confidence: 99%
“…CONCERTA Ò , launched in January 2003, was the first MR MPH, followed by Medikinet Ò retard (launched on February 1, 2005), Equasym Ò Retard (launched on September 15, 2006), and RITALIN LA Ò (launched on December 1, 2007). These formulations overcome the need for the multiple daily doses that are necessary with immediate release (IR) formulations because of their short half-life (Takon 2011), and are generally considered to be as effective as the IR formulations (Coghill and Seth 2006). The MR MPH formulations differ in their MPH release profiles, thereby enabling the physician to match the medication to the patient's particular requirements (Takon 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] The first-line treatment for patients with severe ADHD is considered pharmacological therapy, such as methylphenidate. 8 Curative therapy is not recommended for this disorder because the precise cause is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the presence of learning difficulties increased the likelihood of treatment discontinuation by approximately three-fold in our investigation. It has been suggested that learning difficulties have an impact on adherence to pharmacologic treatment and that ADHD patients with learning difficulties may have a poorer response to pharmacologic treatment compared with those without this comorbidity 4547…”
Section: Discussionmentioning
confidence: 99%